2003
DOI: 10.1291/hypres.26.577
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Uroguanylin, an Intestinal Natriuretic Peptide, on Tubuloglomerular Feedback

Abstract: Uroguanylin is an endogenous peptide that stimulates cyclic guanosine monophosphate (cGMP) production via the activation of guanylate cyclase C (GC-C) in the intestine and kidney. A high salt diet, but not intra-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…These findings indicate that UGN inhibits the major route of sodium reabsorption in renal proximal tubules. Our findings also corroborate other studies that suggested the proximal tubule as a target for the UGN natriuretic effect (14,36,49,51).…”
Section: Discussionsupporting
confidence: 92%
“…These findings indicate that UGN inhibits the major route of sodium reabsorption in renal proximal tubules. Our findings also corroborate other studies that suggested the proximal tubule as a target for the UGN natriuretic effect (14,36,49,51).…”
Section: Discussionsupporting
confidence: 92%
“…They respond to changes in tubular fluid composition by transmitting signals to the afferent arterioles, thereby regulating the preglomerular vascular resistance and filtered load to the tubules (22). This intriguing mechanism has remained under intensive investigation and the accrued evidence indicates that there are multiple interacting paracrine agents involved in the communication pathway between the macula densa cells and the vascular smooth muscle cells (22,88). Because the TGF mechanism participates in autoregulatory responses of the arteriolar vasculature to changes in renal perfusion pressure, it is also recognized that the mediator of the TGF mechanism contributes to the changes in renal vascular resistance (RVR) associated with autoregulatory responses (21,22).…”
Section: Possible Roles Of Adenosine and Atp In The Tubuloglomerular mentioning
confidence: 99%
“…The knockout animals were also found to have increased blood pressure (196). Uroguanylin may complement the renal effects of the cardiac natriuretic peptides, through suppression of the TGF, although its effects on glomerular microcirculation are far less than those of ANP (373).…”
Section: Guanylin and Uroguanylinmentioning
confidence: 99%